Development of a project assessment instrument to measure skills using historical sources for history study program students at the University of Riau - Fikri, Asyrul; Aman, Aman; Suarman, Suarman; Isjoni, Isjoni; Sumarno, Sumarno (Jurnal Ilmu Pendidikan, 2023)
The goal of this study is to create a project evaluation tool that can be used to evaluate students' knowledge of how to use historical sources at the University of Riau's History Study Program. The three steps of the employed instrument development approach are: (i) problem analysis and instrument development needs; (ii) development of a framework for project evaluation instruments; and (iii) validation tests, instrument trials, and instrument changes by experts. 54 randomly chosen students from the history education study program at Riau University made up the research subjects. Research data was gathered through surveys and literature reviews. The SPSS version 25.0 application is used to do statistical analysis as part of the data analysis approach. 4.416. This demonstrates the instrument's excellent design and alignment with the intended use of the measurement. With an average score of 4.24, the test results further demonstrate this instrument's capacity to deliver reliable assessments. The instrument's validity and reliability scored highly. Based on these results, it can be said that the project evaluation tool created in this study has strong validity and reliability in assessing students in the University of Riau's History Study Program's capacity to use historical materials. This test is a useful tool for determining how well students can examine and comprehend historical sources. In the subject of historical education, this study has a significant impact on the creation of project assessment tools and can serve as the foundation for future advancements.